Didactic Strategies for the Strengthening of Academic Writing in University Students from an Innovative Approach - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Buelvas, León Julio Arango (Journal of Ecohumanism, 2024)
This article addresses the design, implementation, and evaluation of didactic strategies aimed at strengthening academic writing in university students. Based on an approach rooted in reflective action and meaningful learning, activities were developed that integrated the review of academic texts, written production, and collaborative feedback. The research was conducted at a higher education institution in Montería, Colombia, with a sample of students from various academic programs. Through a qualitative-descriptive design, the main difficulties in academic writing processes were identified, such as idea organization, argumentation, and proper use of APA norms. The results showed significant improvements in the students’ ability to structure coherent and well-supported texts. This study highlights the importance of implementing innovative strategies in the university context to foster key competencies in academic writing, essential for students’ academic and professional development.